Survival After Methemoglobinemia Associated with Massive Paracetamol Ingestion: A Case Report and Review of the Literature - Geelen, Liesbeth; Verbeke, Koen; Ryckeboer, Jietse; Nieuwendijk, Rogier; Rogiers, Peter (Annals of Anesthesiology and Critical Care, 2019)
Introduction: Paracetamol is a frequently used agent in intoxications and known to cause hepatic failure. However, methemoglobinemia secondary to paracetamol toxicity has only been described in a handful of case reports and may be an important determining factor for morbidity and mortality. Methemoglobinemia results in functional anemia with cellular hypoxia. Severe cases are usually fatal. Case Presentation: We present a case of survival after severe methemoglobinemia in a 67-year-old female. She was admitted to the Intensive Care Unit after auto-ingestion of a large amount of paracetamol. Hemoglobin-oximetry showed a methemoglobin level of 24.6%, treated with intravenous methylene blue, exchange-transfusion, ascorbic acid, and riboflavin. Toxicological screening revealed a high plasma concentration of paracetamol (611.7 mg/L). Treatment with N-acetylcysteine (NAC) was initiated. The patient deteriorated and developed acute liver failure, but refused liver transplantation. Furthermore, she developed septic shock with multi-organ failure and bowel ischemia. In spite of her severe condition and her refusing transplantation, the patient survived. There was a complete resolution of acute liver failure and she fully recovered from her critical condition. Conclusions: A case of survival after paracetamol-induced methemoglobinemia is presented. Paracetamol-induced methemoglobinemia seems to be a rare (but possibly under-diagnosed) condition. With this report, we would like to focus more attention on the possibility of methemoglobinemia associated with paracetamol intoxication and emphasize the possible impact on morbidity and mortality. Therefore, we think there should be a low threshold for screening for this rare but hazardous problem when there is clinical suspicion.